Mahsa Amini protests internet shutdown (Iran) - Voidly (2022)
CRITICAL severity censorship detected in Iran. Confidence: 90%. Data sourced from OONI.
Censorship Incident ID: IR-2022-0004
Keywords: censorship; IR; censorship; critical